Development Of Dragon Fruit Peel-based Snacks Bar - Shee, Wei Yee (Universiti Sains Malaysia, 2021)
This study was aimed to analyse the nutritional composition and physicochemical properties of snack bar formulated with different levels of dragon fruit peel (DFP) powder. Snack bars were prepared with the addition of increasing amount of DFP in 0g, 5g, 10g and 15g respectively. Proximate composition, antioxidant, physical and microbiological properties along with shelf-life study were assessed. The increase in the addition of DFP significantly increase the moisture, ash and crude fibre content (p<0.05), while significantly decrease the fat, protein, carbohydrate content and energy value (p<0.05). There is significant difference in total phenolic content and total flavonoid content (p<0.05) of snack bar between the control and snack bar incorporated with DFP. There is no significant difference (p<0.05) in free radical scavenging activity and ferric reducing antioxidant potential between the control and snack bar incorporated with DFP. The addition of DFP significantly (p<0.05) increase the redness (a*) but shows no significant difference (p<0.05) in lightness (L*) and yellowness (b*) between the control and snack bar incorporated with DFP. Texture profile analysis shows significant difference (p<0.05) in terms of hardness, springiness, cohesiveness and resilience between the control and snack bar incorporated with DFP. The total plate count and yeast and mold count of snack bar is less than 25 cfu/ml which complies to the safety limit for ready-to-eat foods.